2003
DOI: 10.1074/jbc.m210801200
|View full text |Cite
|
Sign up to set email alerts
|

The Islet ॆ Cell-enriched RIPE3b1/Maf Transcription Factor Regulates pdx-1 Expression

Abstract: Pancreatic duodenal homeobox factor-1, PDX-1, is required for pancreas development, islet cell differentiation, and the maintenance of ␤ cell function. Selective expression in the pancreas appears to be principally regulated by Area II, one of four conserved regulatory sequence domains found within the 5-flanking region of the pdx-1 gene. Detailed mutagenesis studies have identified potential sites of interaction for both positive-and negative-acting factors within the conserved sequence blocks of Area II. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 63 publications
6
39
0
1
Order By: Relevance
“…We also reported that loss of RIPE-3b1 binding precedes the loss of PDX-1 binding to the insulin promoter as glucotoxicity develops (8). The chronology of these losses is likely to be important in light of a recent report that RIPE-3b1/MafA directly activates PDX-1 transcription (9).…”
mentioning
confidence: 59%
“…We also reported that loss of RIPE-3b1 binding precedes the loss of PDX-1 binding to the insulin promoter as glucotoxicity develops (8). The chronology of these losses is likely to be important in light of a recent report that RIPE-3b1/MafA directly activates PDX-1 transcription (9).…”
mentioning
confidence: 59%
“…Areas I-II impart islet-specific Pdx1 expression, while Area III working alone can confer b-cell-specific expression . Areas I-II-III harbor binding sites for many TFs such as HNF1a, Pdx1 (Marshak et al, 2000;Gerrish et al, 2001), Foxa2 (Gerrish et al, 2000;BenShushan et al, 2001), Pax6 (Samaras et al, 2002), HNF6 (Jacquemin et al, 2003), and MafA (Samaras et al, 2003). Deletion of the Area I-II-III cis-regulatory region creates a Pdx1 hypomorphic allele (Pdx1 DI-II-III ), and revealed that proper pancreas specification and outgrowth/differentiation from the foregut endoderm requires high Pdx1 levels.…”
Section: Pdx1mentioning
confidence: 99%
“…93 The Pdx1 gene has 4 highly conserved regions viz., Areas I-II-III (the proximal enhancer region) 94 and Area IV (the distal enhancer). 95 Hnf1a, 96 Foxa2, 94 Hnf6, 69 Pax6, 97 and MafA 98 have binding sites within Areas I-II-III whereas Foxa1 and Foxa2 regulate Pdx1 expression via Area IV. 79 Pdx1 regulates b-cell identity by repressing the a-cell program via a shift in transcription profiles.…”
Section: Sex Determining Region Y Box 17 (Sox 17)mentioning
confidence: 99%